2013
DOI: 10.1080/17470218.2012.708761
|View full text |Cite
|
Sign up to set email alerts
|

Shifts of the psychometric function: Distinguishing bias from perceptual effects

Abstract: Morgan, Dillenburger, Raphael, and Solomon have shown that observers can use different response strategies when unsure of their answer, and, thus, they can voluntarily shift the location of the psychometric function estimated with the method of single stimuli (MSS; sometimes also referred to as the single-interval, two-alternative method). They wondered whether MSS could distinguish response bias from a true perceptual effect that would also shift the location of the psychometric function. We demonstrate theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 56 publications
1
72
0
Order By: Relevance
“…3F) is the proportion of incorrect Go responses as a fraction of the total number of all responses (Go + NoGo). Other models have incorporated lapse rates when fitting data with a 2-AUFC-like model (25). Analyzing our data with such models could result in more accurate estimates of the d′ and bias (absolute values), but would not alter our claim regarding the improvements of d′ (relative values) with cueing.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…3F) is the proportion of incorrect Go responses as a fraction of the total number of all responses (Go + NoGo). Other models have incorporated lapse rates when fitting data with a 2-AUFC-like model (25). Analyzing our data with such models could result in more accurate estimates of the d′ and bias (absolute values), but would not alter our claim regarding the improvements of d′ (relative values) with cueing.…”
Section: Discussionmentioning
confidence: 91%
“…3C). The importance and advantages of incorporating such opt-out responses in lieu of the standard 2-AFC design have been highlighted previously (25). Modeling the decision-making process with a 2-AUFC model (indecision model) permitted us to demonstrate that the strategy used by the birds in performing the task was not one of maximizing rewards, but one of maintaining a constant (high) certainty of averting errors when making a Go choice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also shown that lack of bias in TOJ tasks (i.e., ξ 0 .5) does not solve the problem. This is reminiscent of a similar contamination that has the same deleterious effect in 2AFC tasks aimed at estimating psychometric functions and thresholds in detection or discrimination experiments and that can only be surmounted by replacing the binary response format of the 2AFC task with a ternary format in which observers are additionally allowed to give an "I don't know" response García-Pérez, 2010;García-Pérez & Alcalá-Quintana, 2010a, 2010b, 2011a, 2011b, 2012bGarcía-Pérez, Alcalá-Quintana, Woods, & Peli, 2011). These results concur with those of Ulrich (1987) and van Eijk et al (2008) in advising against the use of TOJ tasks in research on perception of temporal order (see also Spence & Parise, 2010).…”
Section: Resultsmentioning
confidence: 99%